Peran Kultur Pesantren dalam Mengkonstruk Nilai Pendidikan Humanistik - Faisol Faisol; Subaidi Subaidi (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
Islam and humanism are two entities that cannot be separated. However, the value of humanism in Islamic educational institutions such as pesantren is rarely highlighted in a wider spectrum. This study aims to describe and analyze the pesantren culture in constructing humanistic values. This study uses a library research approach with reference books and several scientific journals that discuss and examine the educational culture of Islamic boarding schools that accommodate humanistic values. The results show that in educational culture there are humanistic educational values ​​such as equality, compassion, democracy, dialogical approach, justice, tolerance, togetherness, help, peace, pluralism, inclusiveness, positive thinking and honesty. Humanistic education in pesantren is carried out through exemplary methods, habituation, giving advice, rewards and sanctions based on pesantren culture. The kiai figure has a central role in strengthening these humanistic values, both inside and outside the pesantren environment.